(untitled) (Northern International Medical College Journal, 2016)
Background : Neonatal sepsis is a common occurrence and major health problem in Bangladesh and other developing countries, a devastating cause of morbidity and mortality during first 28 days of life. Objective: This study was carried out to evaluate the efficacy of hematological scoring system (HSS) in the early detection of neonatal sepsis. Study period : June 2014 to December 2014(Six months). Methods : This was a prospective study consisting of 218 neonates admitted at Intensive Care Unit (ICU) Dhaka Shishu Hospital who were clinically suspected to have septicaemia. Newborn babies with major congenital anomaly,inborn error of metabolism, severely jaundiced due to blood group incompatibilities or RDS (due to surfactant deficiency) were excluded. The hematological parameter were measured in all cases. Patients were scored according to hematological scoring system (HSS), incorporating increase or decrease in leucocytes count, absolute neutrophil count, immature neutrophil count (e.g. band form), presence of degenerative changes in neutrophil (e.g. toxic granulation, vacuolation). CRP estimation and blood culture were also performed. Blood culture is considered as gold standard for diagnosis of sepsis. Fourteen out of 128 (11%) had culture proven sepsis. They were predominantly preterm and of very low birth weight. Score of 3 was considered as positive. Results : On evaluation of various hematological parameters the HSS was found to have a sensitively of 71%, specificity of 73%, positive predictive value 24%, negative predictive value 95%. Conclusion: HSS is a simple, quick, readily available effective tool to detect early neonatal sepsis. Considering the high sensitivity, specificity, negative predictive value, this study implies that score ³3 were reliable as a screening tool for early neonatal sepsis. Northern International Medical College Journal Vol.7(2) Jan 2016: 135-138